DDIS-26. HIGH-THROUGHPUT DRUG SCREENING OF MENINGIOMAS IDENTIFIES HDAC INHIBITORS AS PROMISING TARGETS ACROSS GRADES. (11th November 2019) - Tatman, Philip; Fringuello, Anthony; Wroblewski, Teddy; Scherer, Sam; Foreman, William; Ryan Ormond, D; Damek, Denise; Lillehei, Kevin; Jensen, Randy; Graner, Michael
Abstract: Meningiomas are a common central nervous system (CNS) tumor, accounting for one third of CNS neoplasms. To date, no FDA approved pharmacotherapy exists for meningiomas. In an effort to identify potential treatments for meningiomas we created a culture system that allows us to grow and screen tumors across hundreds of compounds within two weeks of resection. We screened 32 meningiomas, six of which were World Health Organization (WHO) grade II, against the National Cancer Institute's (NCI) FDA-approved cancer compound library and Caymen Chemical's epigenetic inhibitor library, totaling to more than 300 compounds. The NCI library was screened at 1um, and the Caymen library was screened at 5um. Each library was screened in triplicate, allowing us to calculate statistical significance. We used an MTS assay to determine cell viability after three days. The data was background subtracted and normalized to controls. Significant changes in cell viability were determined for individual drugs using a Mann-Whitney-U test compared to untreated controls. On average, regardless of grade, 5.9 compounds per hundred screened significantly reduced tumor viability. We identified four compounds in the NCI FDA-approved library that reduced cell viability, on average across all tumors screened, by at least 50%: romidepsin, panobinostat, daunorubicin, and carfilzomib. Using the same criteria, we identified the following drugs from the Caymen epigenetic library: LAQ824, panobinostat, and HC toxin. Of the six compounds implicated as possible treatments for meningiomas, four are histone deacetylase (HDAC) inhibitors. HDAC inhibitors may represent a promising target for the treatment of meningiomas. Based on this data, we have begun in vivo work using PDX mouse models to investigate the therapeutic potential of HDAC inhibitors for the treatment of meningiomas.